Emerging Roles of P2X Receptors in Cancer - Elena Adinolfi; Marina Capece; Francesca Amoroso; Elena De Marchi; Alessia Franceschini (2014)
Tumor microenvironment composition strongly conditions cancer growth and progression, acting not only at cancer itself but also modifying its interactions with immune, endothelial and nervous cells. Extracellular ATP and its receptors recently gained increasing attention in the oncological field. ATP accumulates in cancer milieu through spontaneous release, tumor necrosis or chemotherapy exerting a trophic activity on cancer cells, modulating the cross talk among tumor, and surrounding tissues. Accordingly, ATP gated P2X receptors emerged as central players in tumor development, invasion, progression and related symptoms. Indeed, P2X receptors are expressed and are functional not only on tumor cells but also in immune-infiltrate and nearby neurons. In this review, we summarize recent findings on P2X receptors role in tumor cell differentiation, bioenergetics, angiogenesis, metastasis and associated pain, giving an outline of the potential anti-neoplastic activity of receptor agonists and antagonists. Keywords: Cancer, extracellular ATP, P2X2, P2X3, P2X4, P2X5, P2X7, pain.